3-Benzamides and 3,4,5-trimethoxyphenyl amines as calcium channel blockers - Kang, Bohee; Oh, Jung Ae; Lee, Jee Youn; Rhim, Hyewhon; Yune, Tae Young; Choo, Hea-Young Park (Pergamon Press Ltd., 2015)
T- and N-type calcium channels have known for relating to therapy of neuropathic pain which is chronic, debilitating pain state. Neuropathic pain is caused by damage of the somatosensory system. It may be associated with abnormal sensations and pain produced by normally non-painful stimuli (allodynia). Neuropathic pain is very difficult to treat, and only some 40-60% of patients achieve partial relief. For a neuropathic pain therapy, anticonvulsant like Lamotrigine, Carbamazepine and a topical anesthetic such as Lidocaine are used. We synthesized 15 novel amine derivatives and evaluated their activities against T-type and N-type calcium channels by whole-cell patch clamp recording on HEK293 cells. Among the tested compounds, compound 10 showed good inhibitory activity for both T-type and N-type calcium channels with the IC50 value of 1.9 mu M and 4.3 mu M, respectively. Compound 10 also showed good analgesic activity on rat spinal cord injury model. (c) 2015 Elsevier Ltd. All rights reserved.